1995
DOI: 10.1002/hep.1840210608
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the 3-hydroxy, 3-methylglutaryl coenzyme a reductase inhibitor pravastatin on bile composition and nucleation of cholesterol crystals in cholesterol gallstone disease

Abstract: 3-hydroxy,3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors reduce biliary cholesterol saturation index (CSI) in duodenal bile in hypercholesterolemic patients and might be useful for gallstone dissolution. However, preliminary data suggest that these drugs are not effective in this respect. We therefore studied 33 patients with radiolucent gallstones in an opacifying gallbladder who were scheduled for elective cholecystectomy. Patients were treated with 40 mg pravastatin day-1 or placebo during the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
1
17
0
2
Order By: Relevance
“…Secretion of biliary cholesterol, bile acids, and of phospholipids decreased by 46%, 36%, and 51% after pravastatin, respectively. As a consequence, cholesterol saturation of bile remained essentially unchanged as described previously, [57][58][59] although some investigators found a decrease during pravastatin. 23,60 Notably, pravastatin and cerivastatin 61 administration may differ from lovastatin and simvastatin because of less effective lowering of biliary cholesterol saturation compared with bile acid and phospholipid secretion.…”
Section: Discussionsupporting
confidence: 76%
“…Secretion of biliary cholesterol, bile acids, and of phospholipids decreased by 46%, 36%, and 51% after pravastatin, respectively. As a consequence, cholesterol saturation of bile remained essentially unchanged as described previously, [57][58][59] although some investigators found a decrease during pravastatin. 23,60 Notably, pravastatin and cerivastatin 61 administration may differ from lovastatin and simvastatin because of less effective lowering of biliary cholesterol saturation compared with bile acid and phospholipid secretion.…”
Section: Discussionsupporting
confidence: 76%
“…28 In fact, statins are reported to decrease the cholesterol saturation index of duodenal bile and to dissolve gallstones in some patients 48 but not in gallstone patients in general. 49 We have proposed 50 that the identification of common gallstone genes (LITH or GBD) should be based on complementary evidence from (1) genetic studies in mice and/or humans, (2) phenotypic characterization of genetically defined animal models (for example, knockout or transgenic mice), and (3) epidemiological studies defining the overall clinical relevance. All these criteria are fulfilled by ABCG5/G8.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are regarded as a relatively safe medicine, with mild side-effects, even for long-term use in patients with hypercholesterolemia [19], and there have been no reports in which statins increase the risk of gallstone formation [12,20]. Most studies have demonstrated that statins reduce, or do not increase, the cholesterol saturation index in bile [21][22][23][24]. Controversy still exists over the effects of statins on ABCA1 expression in macrophages and other cells [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 97%